ANALISIS TERHADAP SYARAT KEPAILITAN PADA PASAL 2 AYAT (1) Jo. PASAL 8 AYAT (4) UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU (STUDI KASUS PUTUSAN NOMOR 05/Pdt.Sus-Pailit/2019/PN Niaga Jkt. Pst) - Andre Kiemas; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
At this time bankruptcy is very important in the business world. In the business world there must be debtors and creditors. To protect the interests of creditors and debtors, a bankruptcy law is required. This bankruptcy originates from the debtor's inability to pay bills, but in practice it is often the debtor's unwillingness to pay debts that are due and can be collected, so bankruptcy laws are needed to protect both parties, both debtors and creditors. This application for a bankruptcy statement can be submitted by creditors or debtors to the head of the court, so the judge in charge of bankruptcy cases is the panel of judges in the commercial court. In proving bankruptcy in a commercial court, the proof must be done simply or follow the simple proof principles listed in Law Number 37 Year 2004 concerning Bankruptcy and postponement of debt payment obligations. However, problems arise in how the conception of this simple proof occurs, because there is often inconsistency in the interpretation of the conception of simple proof, as well as problems regarding the presence of creditors mentioned in the trial whether they are obliged to attend or not in the trial of the bankruptcy case. So that the authors conducted research to discuss existing problems using normative research methods supported by interview data.